Leptospirosis Associated with the Ingestion of Packaged Foods and Working Environment Conditions: A Case Report - Chavez Pagola Jorge Teodoro; Aguirre Rembao Lorenzo Octavio; Toribio Jimenez Jeiry; Salas Casas Andres; Reynoso Vázquez Josefina; Ruvalcaba Ledezma Jesus Carlos (Journal of Pure and Applied Microbiology, 2018)
The Aim was focused on to describe the diagnosis and evolution of the case of the illness of Weil in male one of 34 years with labor and environmental risk activity to develop Leptospirosis. A case report was realized based on case history, diagnosis, and treatment in hospital. The carried out tests denote the Weil illness with positive answer to the treatment and high out of risk labor and environmental with treatment at home. The labor and environmental conditions suppose risk for leptospirosis, the treatment with doxiciclina/200 mg c/12 hours, with progressive recoverability and treatment at home.